Navigating the Tides of Change: A Comprehensive Analysis of Employment and Unemployment Dynamics in Indonesia - Mulya, Nico Pranata Mulya (Danadyaksa: Post Modern Economy Journal, 2024)
Labor dynamics play a pivotal role in the economic growth of a country. This study aims to fill the research gap by conducting a descriptive analysis comparing the working population and unemployment in Indonesia from 2011 to 2020. Data are sourced from BPS statistical records, including the number of working individuals, unemployed persons, and variables such as wage rates, economic growth, employment opportunities, and education. The study employs descriptive statistical techniques to examine labor trends over the past decade. Key changes in unemployment and employment rates are explored in relation to the global economic crisis, technological advancements, and the COVID-19 pandemic. Findings show an upward trend in employment, while unemployment experienced significant fluctuations, especially during the pandemic, with precise figures illustrating these patterns. The study highlights education, structural transformation, and economic growth as crucial determinants of labor market dynamics, providing more targeted policy implications. These implications offer actionable insights to enhance inclusive growth, improve job quality, and strengthen labor market resilience. The study provides a solid foundation for adaptive and responsive policy formulation aimed at creating a more sustainable employment environment.